2021
DOI: 10.1519/jsc.0000000000002739
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Eccentric and Concentric Knee Strength Capacities and Maximal Linear Deceleration Ability in Male Academy Soccer Players

Abstract: Harper, DJ, Jordan, AR, and Kiely, J. Relationships between eccentric and concentric knee strength capacities and maximal linear deceleration ability in male academy soccer players. J Strength Cond Res XX(X): 000-000, 2018-The purpose of this study was to investigate the relationships between maximal linear deceleration ability, and knee flexor (KF) and knee extensor (KE) strength. Fourteen male academy soccer players completed a 30-m linear sprint, a maximal linear deceleration test, and eccentric and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 35 publications
5
67
1
Order By: Relevance
“…This could be due to the differences in body weight encountered with age: where older players are more likely to be characterized by higher strength levels but have to accelerate a heavier body mass compared to the younger players. On the contrary, absolute lower limb strength may play a fundamental role during deceleration phases and explain the moderate significant correlation with Y-PHV seen in the present study [35].…”
Section: Discussioncontrasting
confidence: 77%
“…This could be due to the differences in body weight encountered with age: where older players are more likely to be characterized by higher strength levels but have to accelerate a heavier body mass compared to the younger players. On the contrary, absolute lower limb strength may play a fundamental role during deceleration phases and explain the moderate significant correlation with Y-PHV seen in the present study [35].…”
Section: Discussioncontrasting
confidence: 77%
“…Maximal horizontal deceleration ability was assessed using a horizontal acceleration–deceleration ability (ADA) test [ 8 ]. Participants were instructed to use the same start protocol employed for the linear sprint test and to sprint maximally over 20 m before performing a maximal horizontal deceleration.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly though, these investigations all concluded that a greater eccentric strength of the quadriceps or hamstrings was beneficially associated with various measures of horizontal deceleration ability (i.e., negative change in velocity, deceleration gradient, time to stop or distance to stop). Additionally, in the study by Harper et al [ 8 ], concentric peak torque measured at higher knee joint angular velocities had the strongest association with both the deceleration distance and time to stop, suggesting that this NMP quality is also an important determinant of horizontal deceleration ability.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations